Détermination des paramètres de transfert de masse de certains composés organiques volatils (COV) dans l’air par simulation - SAIED Miloud (My University, 2013)
The environmental concerns take, nowadays, an unceasingly increasing importance. In this context, the protection of the atmosphere by the control of the gas emissions charged in pollutants becomes a major environmental stake. Among the various sources of pollution of the atmosphere, transmitting industries of rejections charged in Volatile Organic Compound (VOC) are the subject of a special attention. Indeed, the VOC are pollutants proven of the lower atmosphere from their environmental impacts and the human health. The VOC are among the dangerous pollutants. A limitation of the risks associated with the evacuation with these components about the receiving middles imposes a partial or total elimination. The techniques of recovery develop the VOC as a raw material; we count among them the adsorption, condensation, processes of membrane and absorption etc. The aim of this research is the elimination of these VOC by adsorption on a granulated activated carbon, by using the continuous mode (fixed bed). Then we will determine the parameters of mass transfer per simulation by using the model of WILKE- LEE, WAKAO and FUNAZKRI. In this work, a simulation program was carried out for elimination cisdichloroethylene, trichloroethylene and tetrachloroethylene, often present in the air. The influence of several parameters such as the initial concentration of composed in the air, the temperature and velocity of the air on adsorption will be presented.
Keywords: VOC, air, adsorption, model of Wilke-Lee WAKAO and FUNAZKRI